Welt der Technik – technische Welt? - Alpsancar, Suzana; Blanke, Ulf; Nowak, Frauke (Technikfolgenabschätzung – Theorie und Praxis)

Der Einfluss von Internationalisierung, Vermögens- und Kapitalstruktur auf die Konzernsteuerquote im Branchenvergleich - eine empirische Analyse - Sureth-Sloane, Caren; Halberstadt, Alexander; Bischoff, Dennis (Steuer und Wirtschaft)

Income Tax Analysis: A Comparison of Microsimulation versus Group Simulation - Müller, Heiko; Sureth-Sloane, Caren (International Journal of Microsimulation)

Entwicklung und psychometrische Überprüfung eines Messinstruments zur Erfassung pädagogischer Kompetenzen in der universitären Lehrerbildung. - Seifert, Andreas; Hilligus, Annegret Helen; Schaper, Niclas (Lehrerbildung auf dem Prüfstand)

Which ostensive stimuli can be used for a robot to detect and maintain tutoring situations? - Lohan, Katrin Solveig; Vollmer, Anna-Lisa; Fritsch, Jannik; Rohlfing, Katharina; Wrede, Britta (IEEE International Workshop on Social Signal Processing)
In developmental research, tutoring behavior has been identified as scaffolding infants’ learning processes. Infants seem sensitive to tutoring situations and they detect these by ostensive cues [4]. Some social signals such as eye-gaze, child-directed speech (Motherese), child-directed motion (Motionese), and contingency have been shown to serve as ostensive cues. The concept of contingency describes exchanges in which two agents interact with each other reciprocally. Csibra and Gergely argued that contingency is a characteristic ostensive stimulus of a tutoring situation [4]. In order for a robot to be treated similar to an infant, it has to both, be sensitive to the ostensive stimuli on the one hand and induce tutoring behavior by its feedback about its capabilities on the other hand. In this paper, we raise the question whether a robot can be treated similar to an infant in an interaction. We present results concerning the acceptance of a robotic agent in a social learning scenario, which we obtained via comparison to interactions with 8-11 months old infants and adults in equal conditions. We applied measurements for motion modifications (Motionese) and eye-gaze behavior. Our results reveal significant differences between Adult-Child Interaction (ACI), Adult-Adult Interaction (AAI) and Adult- Robot Interaction (ARI) suggesting that in ARI, robotdirected tutoring behavior is even more accentuated in terms of Motionese, but contingent responsivity is impaired. Our results confirm previous findings [14] concerning the differences between ACI, AAI, and ARI and constitute an important empirical basis for making use of ostensive stimuli as social signals for tutoring behavior in social robotics.
Keywords: Ostensive Signals; Contingency; Motionese; hri

Attention via synchrony. Making use of multimodal cues in social learning - Rolf, Matthias; Hanheide, Marc; Rohlfing, Katharina (IEEE Transactions on Autonomous Mental Development)
Infants learning about their environment are confronted with many stimuli of different modalities. Therefore, a crucial problem is how to discover which stimuli are related, for instance, in learning words. In making these multimodal "bindings," infants depend on social interaction with a caregiver to guide their attention towards relevant stimuli. The caregiver might, for example, visually highlight an object by shaking it while vocalizing the object's name. These cues are known to help structuring the continuous stream of stimuli. To detect and exploit them, we propose a model of bottom-up attention by multimodal signal-level synchrony. We focus on the guidance of visual attention from audio-visual synchrony informed by recent adult-infant interaction studies. Consequently, we demonstrate that our model is receptive to parental cues during child-directed tutoring. The findings discussed in this paper are consistent with recent results from developmental psychology but for the first time are obtained employing an objective, computational model. The presence of " multimodal motherese" is verified directly on the audio-visual signal. Lastly, we hypothesize how our computational model facilitates tutoring interaction and discuss its application in interactive learning scenarios, enabling social robots to benefit from adult-like tutoring. Document Type: Article

Gesture as a support for word learning: The case of under - McGregor, Karla K.; Rohlfing, Katharina; Bean, Allison; Marschner, Ellen (JOURNAL OF CHILD LANGUAGE)
Forty children, aged 1;8-2;0, participated in one of three training conditions meant to enhance their comprehension of the spatial term under: the +Gesture group viewed a symbolic gesture for under during training; those in the +Photo group viewed a still photograph of objects in the under relationship; those in the Model Only group did not receive supplemental symbolic support. Children's knowledge of under was measured before, immediately after, and two to three days after training. A gesture advantage was revealed when the gains exhibited by the groups on untrained materials (but not trained materials) were compared at delayed post-test (but not immediate Post-test). Gestured input promoted more robust knowledge of the meaning of under, knowledge that was less tied to contextual familiarity and more prone to consolidation. Gestured input likely reduced cognitive load while emphasizing both the location and the movement relevant to the meaning of under.

Socio-pragmatics and attention: Contributions to gesturally guided word learning in toddlers - Booth, A. E; McGregor, Karla K.; Rohlfing, Katharina (Journal of Language Learning and Development)

Towards a Computational Model of Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina (International Conference on Development and Learning (ICDL 2009))
Keywords: Acoustic Packaging; multimodal

The Structure of Robot-Directed Interaction compared to Adult- and Infant-Directed Interaction using a Model for Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina; Fischer, Kerstin (Spoken Dialogue and Human-Robot Interaction)

Systemic interaction analysis (SInA) in HRI - Lohse, Manja; Hanheide, Marc; Rohlfing, Katharina; Sagerer, Gerhard (Proceedings of the 4th ACM/IEEE international conference on Human robot interaction - HRI '09)
Keywords: SINA; human robot interaction; biron

Which Motionese Parameters Change with Children’s Age? - Vollmer, Anna-Lisa; Lohan, Katrin Solveig; Fritsch, Jannik; Wrede, Britta; Rohlfing, Katharina
Keywords: Contingency; Motionese

Acoustic Packaging - Schillingmann, Lars; Wrede, Britta; Rohlfing, Katharina (HUROBINT2009)

LEK – Längsschnittliche Erhebung pädagogischer Kompetenzen von Lehramtsstudierenden: Testinstrumente, Forschungsdesign und Fragestellungen. - König, Johannes; Seifert, Andreas; Blömeke, Sigrid; Schaper, Niclas (AEPF-Tagung „Selbstregulation – Fremdregulation“)

Welche Dimensionen bzw. Modellstruktur liegt der Messung pädagogischer Kompetenz in der universitären Lehrerausbildung zugrunde? - Seifert, Andreas; Schaper, Niclas (AEPF-KBBB-Tagung)

Tanzeinlagen im Sprechtheater des 19. Jahrhundert - Tumat, Antje (Tanz im Musiktheater – Tanz als Musiktheater: Bericht eines internationalen Symposions über Beziehungen von Tanz und Musik im Theater)

London: Schauspielmusik und Maskenspiele - Tumat, Antje (Händels Opern. Teilband 1)

Dose-dependent melanonychia by mitoxantrone. - Reinsberger, Claus; Meuth, SG; Wiendl, H (Mult Scler)

Die Spezifische Sprachentwicklungsstörung und daraus resultierende Folgeprobleme. - Grosser, Christine

Rapid Room-Temperature Synthesis and Characterization of Nanocrystals of a Prototypical Zeolitic Imidazolate Framework - Cravillon, Janosch; Münzer, Simon; Lohmeier, Sven-Jare; Feldhoff, Armin; Huber, Klaus; Wiebcke, Michael (Chemistry of Materials)
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Nanocrystals of [Cu3(btc)2] (HKUST-1): a combined time-resolved light scattering and scanning electron microscopy study - Zacher, Denise; Liu, Jianing; Huber, Klaus; Fischer, Roland A. (Chemical Communications)
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Formation of Ca2+-Induced Intermediate Necklace Structures of Polyacrylate Chains - Lages, Sebastian; Lindner, Peter; Sinha, Prashant; Kiriy, Anton; Stamm, Manfred; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

On global effects caused by locally noneffective unitary operations - Gharibian, Sevag; Kampermann, Hermann; Bruß, Dagmar (Quantum Information & Computation)
Given a bipartite quantum state rho with subsystems A and B of arbitrary dimensions, we study the entanglement detecting capabilities of locally noneffective, or cyclic, unitary operations [L. B. Fu, Europhys. Lett., vol. 75, pp. 1-7, 2006]. Local cyclic unitaries have the special property that they leave their target subsystem invariant. We investigate the distance between rho and the global state after local application of such unitaries as a possible indicator of entanglement. To this end, we derive and discuss closed formulae for the maximal such distance achievable for three cases of interest: (pseudo)pure quantum states, Werner states, and two-qubit states. What makes this criterion interesting, as we show here, is that it surprisingly displays behavior similar to recent anomalies observed for non-locality measures in higher dimensions, as well as demonstrates an equivalence to the CHSH inequality for certain classes of two-qubit states. Yet, despite these similarities, the criterion is not itself a non-locality measure. We also consider entanglement detection in bound entangled states.

Signatures of nonclassicality in mixed-state quantum computation - Datta, Animesh; Gharibian, Sevag (Physical Review A)
We investigate signatures of non-classicality in quantum states, in particular, those involved in the DQC1 model of mixed-state quantum computation [Phys. Rev. Lett. 81, 5672 (1998)]. To do so, we consider two known non-classicality criteria. The first quantifies disturbance of a quantum state under locally noneffective unitary operations (LNU), which are local unitaries acting invariantly on a subsystem. The second quantifies measurement induced disturbance (MID) in the eigenbasis of the reduced density matrices. We study the role of both figures of non-classicality in the exponential speedup of the DQC1 model and compare them vis-a-vis the interpretation provided in terms of quantum discord. In particular, we prove that a non-zero quantum discord implies a non-zero shift under LNUs. We also use the MID measure to study the locking of classical correlations [Phys. Rev. Lett. 92, 067902 (2004)] using two mutually unbiased bases (MUB). We find the MID measure to exactly correspond to the number of locked bits of correlation. For three or more MUBs, it predicts the possibility of superior locking effects.

Factoring polynomials over global fields - Belabas, Karim; van Hoeij, Mark; Klüners, Jürgen; Steel, Allan (Journal de Théorie des Nombres de Bordeaux)
We prove that van Hoeij’s original algorithm to factor univariate polynomials over the rationals runs in polynomial time, as well as natural variants. In particular, our approach also yields polynomial time complexity results for bivariate polynomials over a finite field.
Keywords: Algebra and Number Theory

The van Hoeij Algorithm for Factoring Polynomials - Klüners, Jürgen (The LLL Algorithm)
In this survey, we report about a new algorithm for factoring polynomials due to Mark van Hoeij. The main idea is that the combinatorial problem that occurs in the Zassenhaus algorithm is reduced to a very special knapsack problem. In case of rational polynomials, this knapsack problem can be very efficiently solved by the LLL algorithm. This gives a polynomial time algorithm, which also works very well in practice.

Social Networking Sites and the Surveillance Society. A Critical Case Study of the Usage of studiVZ, Facebook, and MySpace by Students in Salzburg in the Context of Electronic Surveillance - Fuchs, Christian

Practical Civil Virtues in Cyberspace: Towards the Utopian Identity of Civitas and Multitudo. Munich Series in Design Science (Münchener Schriften zur Design Science) - Fuchs, Christian; E. Zimmermann, Rainer

Some Reflections on Manuel Castells’ Book “Communication Power“ - Fuchs, Christian (tripleC (Cognition, Communication, Co-operation) – Open Access Journal for a Global Sustainable Information Society)

A fenntartható információs társadalom ideológiai tájképe. 2. rész (Sustainable Information Society as Ideology. Second Part, in Hungarian) - Fuchs, Christian (Információs Társadalom (Information Society))

A fenntartható információs társadalom ideológiai tájképe. 1. rész (Sustainable Information Society as Ideology. First Part, in Hungarian) - Fuchs, Christian (Információs Társadalom (Information Society))

Some Theoretical Foundations of Critical Media Studies: reflections on Karl Marx and the media - Fuchs, Christian (International Journal of Communication 3 (2009))

The role of income inequality in a multivariate cross- national analysis of the digital divide - Fuchs, Christian (Social Science Computer Review)

Cyberethics and Co- operation in the Information Society - Fuchs, Christian; Bichler, Robert; Raffl, Celina (Science and Engineering Ethics)

A Contribution to Theoretical Foundations of Critical Media and Communication Studies - Fuchs, Christian (Javnost-The Public)

Internet und Gesellschaft: Beiträge zu einer kritischen Theorie des Informationszeitalters [Internet and Society: Contibutions to a Critical Theory of the Information Age] - Fuchs, Christian (Neue Medien und kulturelle Vielfalt [New Media and Cultural Diversity])

Grundlagen der Kritik der Politischen Ökonomie der Medien [Foundations of the critique of the political economy of the media] - Fuchs, Christian (Bruchstücke: Kritische Ansätze zu Politik und Ökonomie im globalisierten Kapitalismus)

Towards a Critical Theory of Information - Fuchs, Christian (tripleC (cognition, communication, co-operation): Journal for a Global Sustainable Information Society)

Autopoiesis and Critical Social Systems Theory - Fuchs, Christian; Hofkirchner, Wolfgang (Autopoiesis in Organization Theory and Practice)

Kapitalistische Medien und kapitalistische Krise [Capitalist media and capitalist crisis] - Fuchs, Christian (Kapitalismus am Ende? [The end of capitalism?])

Conference Report: The Internet as Playground and Factory (November 12-14, 2009, The New School, New York City, USA) - Fuchs, Christian (tripleC)

Ordered Mesoporous In2O3: Synthesis by Structure Replication and Application as a Methane Gas Sensor - Waitz, Thomas; Wagner, Thorsten; Sauerwald, Tilman; Kohl, Claus-Dieter; Tiemann, Michael (Advanced Functional Materials)
The synthesis and characterization of ordered mesoporous In2O3 materials by structure replication from hexagonal mesoporous SBA-15 silica and cubic KIT-6 silica is presented. Variation of the synthesis parameters allows for different pore sizes and pore wall thicknesses in the products. The In2O3 samples turn out to be stable up to temperatures between 450 °C and 650 °C; such high thermal stability is necessary for their application as gas sensors. Test measurements show a high sensitivity to methane gas in concentrations relevant for explosion prevention. The sensitivity is shown to be correlated not only with the surface-to-volume ratio, but also with the nanoscopic structural properties of the materials.

Time-resolved photoluminescence study of mesoporous ZnO nanostructures - Schwalm, Michael; Horst, Swantje; Chernikov, Alexej; Rühle, Wolfgang W.; Lautenschläger, Stephan; Klar, Peter J.; Meyer, Bruno K.; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (physica status solidi (c))
We report a systematic study of the photoluminescence properties of ZnO nanostructures. In particular, mesoporous ZnO powders of varying surface-to-mass ratio are investigated and compared to a bulk reference. At low temperatures the emission from higher-energy states is very pronounced and even dominant for samples with high surface-to-mass ratio.

Social Networking Sites and the Surveillance Society - Allmer, Thomas; Sandoval, Marisol (American Philosophical Association Newsletter on Philosophy and Computers)

Morals in the world-picture - Matzner, Tobias (Sprache und Welt: Beiträge des 32. Internationalen Wittgenstein Symposiums)

Learning Parametrised RoboCup Rescue Agent Behaviour Using an Evolutionary Algorithm - Kruse, Michael; Baumann, Michael; Knieper, Tobias; Seipel, Christoph; Khaluf, Lial; Lehmann, Nico; Lermontow, Alex; Messinger, Christian; Richter, Simon; Schmidt, Thomas; Swars, Daniel

Coupling Dynamics of Quantum Dots in a Liquid-Crystal-Tunable Microdisk Resonator - Förstner, Jens; Meier, Cedrik; Piegdon, Karoline; Declair, Stefan; Hoischen, Andreas; Urbanski, Mark; Meier, Torsten; Kitzerow, Heinz-Siegfried (Advances in Optical Sciences Congress)
We experimentally and theoretically investigate microdisk resonators with embedded quantum dots immersed in a liquid crystal in its nematic phase, showing the tunabililty of the photonic modes via external parameters like temperature or electric field.
Keywords: tet_topic_microdisk

Konsumgesellschaft - Kleinschmidt, Christian (Sic et Non. Zeitschrift Philosophie / Kultur im Netz)

Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten

Schäfer, Friedrich August (1883-1958) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Foerster, Gotthilf Helmut (1895-1964) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Lehmbruck, Wilhelm (1881-1919) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Sehlbach, Erich (1898-1985) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Weigle, Maria (1893-1979) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bunk, Gerard (1888-1958) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Heyne, Bodo (1893-1980) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Peters, Ilse - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Biblische Bilder - Beobachtungen zur Transformation der Bibel in der Klaviermusik in Deutschland im 19. und 20. Jahrhundert - Schroeter-Wittke, Harald (Inszenierungen der Heiligen Schrift. Jüdische und christliche Bibeltransformationen vom Mittelalter bis in die Moderne)

Ruhrgebietsperikopenreihe. Wir werden aber alle verwandelt werden (1 Kor 15,51b). Mit der Bibel durch RUHR 2010. Eine Perikopenreihe für das Ruhrgebiet - Schroeter-Wittke, Harald (Wir werden aber alle verwandelt werden. Handreichung zu den "Local Hero Wochen" in der Kulturhauptstadt RUHR 2010)

Heilige Scheu und profane Hygiene. Abendmahl als Zeichen der Nähe - Zwischen Scham und Verbundenheit - Schroeter-Wittke, Harald (Näher! 7 Wochen ohne Scheu. Arbeitshilfe zum Thema "Näher!")

"Zur Recreation des Gemüths" - Musik als Seelsorge - Schroeter-Wittke, Harald (Seelsorge heute. Aktuelle Perspektiven aus Theorie und Praxis)

Hören - Theologische Hermeneutik populärer Hörwelten - Schroeter-Wittke, Harald (Sinnspiegel. Theologische Hermeneutik populärer Kultur)

Big Boss oder: Im Spiel üben wir Verlieren-Können. 10 zuversichtliche Mutmaßungen zum Brettspielen von Erwachsenen - Schroeter-Wittke, Harald (Erwachsen werden - Erwachsen sein)

Prophetie zwischen Zeitansage und Bibelgebrauch - Impulse der biblischen Prophetie für die Praxis der Christinnen und Christen heute - Schroeter-Wittke, Harald (Erziehen heute)

Popkultur und Religion - Best of...

Ultrafast Coherent Interactions in Quantum Wells Studied by Two-Dimensional Fourier Transform Spectroscopy - Meier, Torsten; Zhang, Tianhao; Kuznetsova, Irina; Yang, Lijun; Bristow, Alan D; Dai, Xingcan; Li, Xiaoqin; Thomas, P.; Mukamel, S.; Mirin, Richard P.; Cundiff, S.T. (Ultrafast Phenomena XVI: Proceedings of the 16th International Conference, Palazzo dei Congressi Stresa, Italy, June 9--13, 2008)

Generation and time‐resolved detection of coherently controlled electric currents at surfaces - Meier, Torsten; Güdde, Jens; Rohleder, M.; Koch, S.W.; Höfer, Ulrich (physica status solidi c)
We demonstrate a technique for the generation and detection of electron currents at surfaces on a femtosecond time scale with a contact-free experimental setup based on a combination of coherent control and photoemission spectroscopy. We have applied this technique for electrons excited into image-potential states on a Cu(100) surface that form a free-electron-like band in the direction parallel to the surface. The photogeneration of currents is described by optical Bloch equations for a multiband model. By incorporating field-induced interband and intersubband transitions together with intraband accelerations into the model, the observed phase dependence of the population and of the current can be reproduced.

Incremental forming of tubes and sheets assisted by friction-induced heating - Homberg, Werner; Hornjak, Daniel; Beerwald, Charlotte; Rostek, Tim; Kunert, Joachim; Wilk, D.

Information and Communication Technologies & Society: A Contribution to the Critique of the Political Economy of the Internet - Fuchs, Christian (European Journal of Communication)

A Contribution to the Critique of the Political Economy of Transnational Informational Capitalism - Fuchs, Christian (Rethinking Marxism)

Review of “The Problem of Order in the Global Age“ (Andreas Pickel) - Fuchs, Christian (tripleC)

A Contribution to Critical Globalization Studies. Centre for the Critical Study of Global Power and Politics Working Paper CSGP 09/8 - Fuchs, Christian

Gas sensor based on ordered mesoporous In2O3 - Wagner, T.; Sauerwald, T.; Kohl, C.-D.; Waitz, T.; Weidmann, C.; Tiemann, Michael (Thin Solid Films)
We present the preparation of a semiconductor gas sensor based on ordered mesoporous In2O3. The In2O3 was synthesized by structure replication procedure from cubic KIT-6 silica. A detailed analysis of the morphology of the mesoporous powders as well as of the prepared sensing layer will be shown. Unique properties arise from the synthesis method of structure replication such as well defined porosity in the mesoporous regime and nanocrystallites with high thermal stability up to 450 °C. These properties are useful for the application in semiconducting gas sensors. Test measurements show sensitivity to methane gas in concentrations relevant for explosion prevention.

Halbleitende Metalloxide als Gassensoren im Chemieunterricht - Waitz, Thomas; Tiemann, Michael (CHEMKON)
Halbleitende Metalloxid-Gassensoren werden sowohl im industriellen Bereich als auch im Haushalt zur Luftüberwachung verwendet. Die Funktionsweise basiert auf einer reversiblen Änderung des Sensorwiderstandes in Anwesenheit sowohl oxidierender als auch reduzierender Gase, die mit einfachen Mitteln gemessen werden kann. In diesem Artikel wird vorgestellt, wie sich die bei der Gasdetektion ablaufenden Vorgänge mit Hilfe des Ionosorptionsmodells in Kombination mit einem einfachen Festkörperbändermodell deuten lassen. Abschließend werden einfache, im Chemieunterricht zu realisierende Experimente mit Gassensoren präsentiert.

Autonomous Sensor Nodes for Aircraft Structural Health Monitoring - Becker, Thomas; Kluge, Martin; Schalk, Josef; Tiplady, Keith; Paget, Christophe; Hilleringmann, Ulrich; Otterpohl, Tobias (IEEE Sensors Journal)
Keywords: Electrical and Electronic Engineering; Instrumentation

Efficient Antenna Design of Inductive Coupled RFID-Systems with High Power Demand - Reinhold, Christian; Scholz, Peter; John, Werner; Hilleringmann, Ulrich (Journal of Communications)
Keywords: Electrical and Electronic Engineering

N-type single nanoparticle ZnO transistors processed at low temperature - Wolff, Karsten; Hilleringmann, Ulrich (2009 Proceedings of the European Solid State Device Research Conference)

Lock Detection for Charge-Pump Phase-Locked Loops - Wiegand, C; Hedayat, C; Hilleringmann, Ulrich (Sophia Antipolis Microelectronics SAME)

Finite symplectic matrix groups (Dissertation) - Kirschmer, Markus
Die invarianten Formen aus dem Anhang sind hier verfügbar:http://www.math.rwth-aachen.de/homes/Markus.Kirschmer/symplectic/

von der Leyen zu Bloemersheim, Friedrich Heinrich Freiherr (1769-1825) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

von Kotzebue, August Friedrich Ferdinand (1761-1819) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Möller, Anton Wilhelm Peter (1762-1846) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Meister, Christoph Georg Ludwig (1738-1811) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Summermann, Caspar Theodor (1674-1752) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Carstanjen, Conrad Jacob (1763-1840) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Jorissen, Matthias (1739-1823) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

von Holy, Gerhard (1677-1736) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Cornelius Friedrich Adolf (1824-1884) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Bisping, Maximilian Anton Wilhelm (1817-1890) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Gottfried Daniel (1774-1837) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Ettling, Georg Friedrich Ludwig (1873-1942) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Lahusen, Christoph Friedrich (1851-1927) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Hoesch, Karl Albert Alexander (1847-1898) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Krummacher, Emil Wilhelm (1798-1886) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Olimart, Franz (1869-1943) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Keßler, Gerda, geb. Bertram (1911-1983) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Brevier fürs Revier. Mit der Bibel durch RUHR.2010

Siemoneit, Hans Rudolf (1927-2009) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Hüsch, Hanns Dieter (1925-2005) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)

Rutenborn, Günter (1912-1976) - Schroeter-Wittke, Harald (Protestantische Profile im Ruhrgebiet. Fünfhundert Lebensbilder aus fünf Jahrhunderten)